191 Role of mir-214 in angiotensin ii induced hypertensive heart disease. (5th June 2017) - McGinnigle, Eilidh; Nosalski, Ryszard; Skiba, Dominik; Denby, Laura; Graham, Delyth; Baker, Andrew H; Guzik, Tomasz J
Abstract : Background: Cardiac dysfunction is one of the hallmarks of hypertension. It is characterised by cardiac fibrosis, diastolic dysfunction and development of heart failure. The mechanisms of hypertensive heart disease are not fully understood. Recent studies suggest a role of miR-214 in regulation of fibrosis. Thus, the aim of this work is to investigate the role miR-214 has in the cardiac sequelae of hypertension. Methods: Hypertension was induced in three month old miR-214 knock out (KO) and wild type (WT) littermates using 490 ng/kg/min angiotensin II (Ang II) for 14 or 28 days (n=4–6). Blood pressure was monitored by tail cuff plethysmography. Cardiac fibrosis was assessed by picrosirius red and Massons trichrome staining. Mir214 expression was assessed by Taqman and in situ hybridisation (ISH). Cardiac function was assessed by echocardiography. Effects of Ang II on fibrosis genes was studied in primary cardiac fibroblasts. Results: 14 day Ang II infusion caused 4-fold induction of miR-214 in the left ventricle of C57bl/6 mice (p<0.001) which was confirmed by ISH. Loss of miR-214 was associated with increased cardiac fibrosis in picosirius red (2.8%±0.52 vs. 4.8%±0.7; p<0.005) caused by Ang II, without effect on blood pressure. This was associated in a significant up-regulation of COL1A1 mRNA compared with their WT littermates (p<0.01). Echocardiography revealed enhanced development of ventricular wall thickening and diastolic dysfunction in mir214 KO when compared to WT mice (E/A ratio: 1.79±0.39 vs 0.59±0.04; p<0.05). In contrast to in vivo observations, in vitro fibroblast studies show that KO fibroblasts showed significantly reduced induction of COL1A1 (p<0.05) and COL3A1 (p<0.05) compared with WT fibroblasts upon Ang II and IL-17 suggesting that involvement of miR-214 in cardiac dysfunction is not directly modulated by the effects in fibroblasts but through other mechanisms that need to be further addressed. Conclusions: Cardiac fibrosis, hypertrophy and diastolic dysfunction are enhanced in miR-214 KO animals. The mechanisms of this observation are not caused by mir214 effects in cardiac fibroblasts, but through other mechanisms that need to be further addressed.